Undergraduates’ Increased Acceptance And Positive Attitude Toward Gamification: Its Relation To Increased Engagement - Feroz, Farah Shahnaz; M. Subramaniam, Indra Devi; Subramaniam, Siva Kumar (Common Ground Research Networks, 2020)
This article aims to investigate the impact of Kahoot! on undergraduates’ engagement in an Engineering Statistics course. A gamification tool, Kahoot! was implemented in an Engineering Statistics undergraduate course to address the needs of undergraduates to be actively engaged during lectures. Based on a survey of seventy-two undergraduates, more than 90 percent agreed that Kahoot! enhanced their learning performance and engagement during lessons. In accordance with the Gamification Acceptance Model, perceived usefulness and perceived ease of use are positively correlated with undergraduates’ attitude. Further, perceived usefulness, perceived ease of use, and increased positive attitude toward Kahoot! are significantly related to increased study skills and interaction engagement. The present study demonstrated that it is possible to effectively engage engineering undergraduates in a statistics course with the implementation of Kahoot!